Portfolio decisions on life annuities and financial assets with longevity and income uncertainty - Susanne Pech (Johannes Kepler University of Linz, Department of Economics, 2004)
There are two stylised facts, namely weak demand for life-annuities and flat age-wealth profile that contradict the life-cycle hypothesis. In this paper we design a theoretical framework, which combines plausible arguments, which have been put forward in the literature to reconcile theory with empirical evidence. Besides the existence of an annuity market and of a public pension system we assume risk-averse individuals who are uncertain about lifetime and disposable income and who have preferences for leaving bequests. It is shown that this framework can contribute to explain the observed portfolio decision in favour of financial assets relatively to annuities.
Keywords: D81; D91; G22; H55; 330; savings; life annuities; bequests; uncertain lifetime; uncertain income; social security; Anlageverhalten; Alterssicherung; Erbe; Lebenszyklus; Risikoaversion; Zeitpräferenz; Leibrente; Entscheidung bei Unsicherheit